Analysis of Social Behavior of Grade IV Students of SD Negeri Rancamulya in Learning Penjas Pthere is a Transition Period of the Covid-19 Pandemic - Ilham Mirdad; Anggi Setia Lengkana; Encep Sudirjo (STKIP Muhammadiyah Kuningan, 2023)
Physical Education has one goal to develop social behavior; the age at primary school is very vulnerable to developing social behavior. So this study aims to analyze the social behavior of grade IV students during the physical education learning process during the transition period of the Covid-19 pandemic. This study used a descriptive qualitative phenomenological approach at SD Negeri Rancamulya with a sample of physical education teachers, principals, and all fourth-grade students. Data collection techniques used in-depth interviews, passive participatory observation, documentation, and data analysis using a network analysis model and data validity based on data triangulation. The study results show that social behavior is seen during physical education, such as; ridicule/disturbing, fighting/fighting, lack of respect/respect, and saying rude/dirty words. Almost all of the social behavior that occurred was negative due to the impact of the Covid-19 pandemic; this can be used as material for evaluating teachers in improving better learning and emphasizing the inculcation of character education in Physical Education learning in the transition period and the importance of parental attention to children.